2015
DOI: 10.1007/s00520-014-2573-9
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics and concerns of female cancer patients/survivors seeking treatment at a Female Sexual Medicine Program

Abstract: Purpose To characterize patients seeking treatment at a Female Sexual Medicine and Women’s Health Program and examine their sexual/vaginal health issues. Methods Data from clinical assessment forms were extracted from 509 women referred to the Female Sexual Medicine and Women’s Health Program during/after cancer treatment. The form consists of a Vaginal Assessment Scale [VAS], vaginal health items, patient-reported outcomes (PROs) (Sexual Activity Questionnaire [SAQ], Sexual Self-Schema Scale [SSS], Female S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Women with vaginal dryness may benefit from the use of vaginal moisturizers and water or silicone‐based lubricants during intercourse, as recommended by the International Menopause Society for postmenopausal women without a cancer history . If available, referral for counseling and/or sexual health programs may be beneficial …”
Section: Assessment and Management Of Physical And Psychosocial Long‐mentioning
confidence: 98%
See 1 more Smart Citation
“…Women with vaginal dryness may benefit from the use of vaginal moisturizers and water or silicone‐based lubricants during intercourse, as recommended by the International Menopause Society for postmenopausal women without a cancer history . If available, referral for counseling and/or sexual health programs may be beneficial …”
Section: Assessment and Management Of Physical And Psychosocial Long‐mentioning
confidence: 98%
“…Multiple studies have shown a strong correlation between sexual dysfunction and psychosocial distress . Thus, primary care clinicians should address sexual function when managing CRC survivors.…”
Section: Assessment and Management Of Physical And Psychosocial Long‐mentioning
confidence: 99%
“…Vaginal dryness can be a major problem to those women who wish to have sex [27], and appropriate vaginal moisturizers and lubricants can help. The issue of vaginal estrogen is still debated, but should be discussed with the patient, weighing up the risk − benefit ratio for each individual.…”
Section: Treatment Strategies For Sexual Problemsmentioning
confidence: 99%
“…3 Vulvovaginal health is impacted by reduced estrogen and results in symptoms of dryness, decreased lubrication and elasticity, irritation, and discomfort of the vaginal and vulvar tissues. 1,2 Unfortunately, there are a lack of clinical tools that effectively address vulvovaginal health concerns beyond the realm of sexual activity.…”
Section: Introductionmentioning
confidence: 99%